Pengaruh Intervensi Aku Anak Hebat Berbasis Body Safety Training terhadap Kemampuan Mengenal “Good Person” sebagai Pelaku Potensial Kekerasan Seksual pada Anak - Marshadina Salma Putri; Indri Utami Sumaryanti (UNISBA Press, 2024)
Abstract. Recently, cases of child sexual abuse have been on the rise. In Indonesia, according to KemenPPPA, there is an increase, namely 9,588 cases per year 2022, where in 2021 there were 8,730 cases. Therefore, there is an intervention, Aku Anak Hebat, which has been adapted from Body Safety Training, which aims to teach children to recognize situations that have the potential for sexual violence, both inside and outside the home. This is in line with the fact that many perpetrators of sexual violence are people closest to the victim, such as parents, friends, neighbors. Thus, children need the ability to recognize that people they know well can become perpetrators of sexual violence. This study aims to determine the effect of the intervention Aku Anak Hebat based on Body Safety Training on the ability to recognize